Effect of plant growth promoting rhizobacteria on seed borne fungal pathogens in okra - and S. LOKESH, MASHOODA BEGUM, V. RAVISHANKAR RAI* (Indian Phytopathology, 2003)
The effectiveness of plant growth promoting rhizobacteria isolates was tested against some seed borne fungal diseases. Among them B. pumilus (SE-34), B. pasteurii (T4), B. subtilis (IN937-b) and B. subtilis (GB03) strains stood first in the improvement of crop both in green-house and field. Potential strains increased the biomass of plants, total number of leaves, fruits, mean length, girth, biomass of the fruits. Apart from these the total number of seeds per fruit, 1000 seed weight were also enhanced. The colonization of these bacterial strains reduced the incidence of seed mycoflora which indirectly enhanced the % seed germination and vigour index of seedlings.